(untitled) - Crichton, Michael (New York, 1999)
On the threshold of the twenty-first century, in a world of amazing advances on the frontiers of technology, information moves instantly between two points, without wires or networks, and computers are built from single molecules. Any moment of the past can be actualized, and a group of historians decide to enter life in fourteenth-century feudal France, a journey not without risks.
Keywords: English language,Ngôn ngữ Anh; Study and teaching,Học và dạy